Optimizing maize yield and nutritional quality through synergistic use of guinea pig manure and mineral fertilization: a sustainable approach for coastal Peru - Calero Rios, Emilee Nahomi (2026)
Introduction: Excessive reliance on mineral fertilizers in maize cultivation has raised environmental concerns, highlighting the need for more sustainable alternatives. This study evaluated the effects of guinea pig (Cavia porcellus L.) manure and the application of N, P and K fertilizers on the yield and nutritional quality of hybrid maize grown in the central Peruvian coast. Methods: A split-plot design with three replications, was implemented, testing four manure doses (0, 2, 5, 10 t ha⁻¹) in combination with four mineral fertilizer levels (0, 50, 75, and 100% of recommended N, P and K). Results: The 5 t ha⁻¹ manure + 75% mineral fertilizer treatment achieved the highest yield (8.82 t ha⁻¹), representing a 28.38% increase relative to the full mineral fertilization treatment, accompanied by a grain weight of 152.80 g and an ear weight of 171.31 g. Nutritional quality peaked at 5 t ha⁻¹ manure + 100% mineral fertilizer, with 7.85% protein and 363 kcal 100 g⁻¹ energy content. Multivariate analysis revealed strong positive correlations between combined organic-mineral inputs and key productivity parameters. These findings demonstrate that the strategic integration of 5 t ha⁻¹ of guinea pig manure with a 25% reduction in mineral fertilization (i.e., 75% of the recommended dose) enhanced both grain yield and nutritional value. Discussion: This combination offers a practical, cost-effective pathway for smallholder farmers to improve yellow maize production under coastal Peruvian conditions while reducing dependence on chemical fertilizers. These results demonstrate a clear synergistic interaction between organic and mineral fertilization, leading to improved crop productivity under conditions of limited soil organic matter in the coastal soils of Peru. This finding supports the use of guinea pig manure as a sustainable and environmentally friendly agricultural input.